The Strategy of Arabic Language Teachers in Implementing Differentiated Learning in the Merdeka Curriculum - Abidah, Zakiyatul (Funun Arabiyyah: Journal of Arabic Education and Literature, 2025)
This research aims to deeply examine the strategies used by Arabic language teachers in implementing differentiated learning in the Merdeka Curriculum at Jatirenggo State Elementary School Glagah Lamongan. The background of this study is based on the importance of applying a learning approach that is responsive to the individual learning needs of students in order to create inclusive, adaptive, and student-centered learning. The Merdeka Curriculum provides teachers with the flexibility to design learning that suits the characteristics of students, thus requiring teachers to have specific strategies to manage differentiated learning, especially in the Arabic language subject, which has its own complexities. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of Arabic language teachers at the institution. The research results show that Arabic language teachers implement three main forms of differentiation strategies, namely content differentiation, process differentiation, and product differentiation. Content differentiation is carried out through the presentation of materials that are varied visually and audibly, as well as the use of digital learning media. Process differentiation is implemented through grouping students based on their initial abilities and providing tiered assignments. Meanwhile, product differentiation focuses on giving students the freedom to choose the final form of their assignments, such as creating dialogues, posters, or recordings of conversations. Teachers also adapt their teaching styles based on students' learning styles (visual, auditory, kinesthetic).